Моделювання невзаємної фотонно-кристалічної структури - Корсун, Г. А. (ХНУРЕ, 2025)
Photonic crystal structure containing linear waveguide and resonator is considered. Package MEEP is used for simulation and investigation of dispersion and spectral characteristics of the photonic crystal system. Fano resonances that realized at spectral characteristics are considered. Non-reciprocal phenomena inherent in the system under study when the direction of the electromagnetic wave motion in the photonic crystal waveguide changes are studied for different values of the system parameters.
Keywords: фотонно-кристалічна структура; Photonic crystal structure